Robert S. McNamara papers - McNamara, Robert S., 1916-2009.; Blight, James G.; McNamara, Robert S., 1916-2009.; McNamara, Robert S., 1916-2009.; McNamara, Robert S., 1916-2009.
Correspondence, memoranda, speeches, writings, reports, oral history transcripts, organization records, subject files, conferences and meetings files, background and research material, and other papers relating primarily to McNamara's private and public life following his service as U.S. secretary of defense, including his leadership of the World Bank, his role as counselor and adviser to various private corporations and nonprofit organizations and foundations, and his commentary on and advocacy for solutions to the critical domestic and foreign policy issues of the times. Includes drafts of his books, In Retrospect : The Tragedy and Lessons of Vietnam (1995) and Argument Without End : In Search of Answers to the Vietnam Tragedy (1999) as well as drafts of Wilson's Ghost : Reducing the Risk of Conflict, Killing, and Catastrophe in the 21st Century co-written by McNamara and James G. Blight (2001).
Subjects include arms control and nuclear policy; defense; domestic and international politics; East-West relations; economic policy; education, food, and health programs; environment; geopolitical issues; international development; onchocerciasis (river blindness); population; poverty; Third World countries in Africa and elsewhere; war and peace; and world hunger. Other subjects include McNamara's legacy as a leading strategist of the Vietnam War, the Cuban Missile Crisis of 1962, and Westmoreland v. CBS et al., 1984-1985.
Documents McNamara's association with organizations and conferences including the African Development Bank, Aspen Institute, Atlantic Council of the United States, Battelle Memorial Institute, Brookings Institution, Carnegie Endowment for International Peace, Charles F. Kettering Foundation, Corning Incorporated, Council on Foreign Relations, Drug Strategies, East African Development Bank, Eminent Persons Group on Curbing Illicit Trafficking in Small Arms and Light Weapons, Enterprise Foundation, Global Coalition for Africa, Henry L. Stimson Center, Honorary Presidential Advisory Council on Investment in Nigeria, Indira Gandhi Memorial Trust, InterAction Council, International Irrigation Management Institute, National Committee on United States-China Relations, Overseas Development Council, Pugwash Conference on Science and World Affairs, Rockefeller Foundation, Trilateral Commission, Urban Institute, World Food Prize Foundation, and World Resources Institute.
Correspondents include Graham T. Allison, James G. Blight, McGeorge Bundy, William P. Bundy, Lloyd N. Cutler, Alain C. Enthoven, Orville L. Freeman, Kurt Gottfried, Pamela Digby Churchill Hayward Harriman, W. Averell Harriman, Paul Hendrickson, Henry Kissinger, Frans M. Lurvink, Helmut Schmidt, Sargent Shriver, Gerard C. Smith, Carl E. Taylor, Stewart L. Udall, Cyrus R. Vance, and Barbara Ward.
Library of Congress Motion Picture, Broadcasting and Recorded Sound Division.
Library of Congress Prints and Photographs Division.
U.S. secretary of defense, president of World Bank, and corporate executive. Full name: Robert Strange McNamara.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Allison, Graham T. -- Correspondence; Blight, James G. -- Correspondence; Bundy, McGeorge -- Correspondence; Bundy, William P., -- 1917- -- Correspondence; Cutler, Lloyd N. -- Correspondence; Enthoven, Alain C., -- 1930- -- Correspondence; Freeman, Orville L. -- Correspondence; Gottfried, Kurt -- Correspondence; Harriman, Pamela Digby Churchill Hayward, -- 1920-1997 -- Correspondence; Harriman, W. Averell -- 1891-1986 -- Correspondence; Hendrickson, Paul, -- 1944- -- Correspondence; Kissinger, Henry, -- 1923- -- Correspondence; Lurvink, Frans M. -- Correspondence; Schmidt, Helmut, -- 1918 December 23- -- Correspondence; Shriver, Sargent, -- 1915-2011 -- Correspondence; Smith, Gerard C. -- Correspondence; Taylor, Carl E. -- Correspondence; Udall, Stewart L. -- Correspondence; Vance, Cyrus R. -- 1917-2002 -- Correspondence; Ward, Barbara, -- 1914-1981 -- Correspondence; Westmoreland, William C. -- 1914-2005 -- Trials, litigation, etc; African Development Bank; Aspen Institute; Atlantic Council of the United States; Battelle Memorial Institute; Brookings Institution; Carnegie Endowment for International Peace; CBS Inc. -- Trials, litigation, etc; Charles F. Kettering Foundation; Corning Incorporated; Council on Foreign Relations; Drug Strategies (Organization); East African Development Bank; Eminent Persons Group on Curbing Illicit Trafficking in Small Arms and Light Weapons; Enterprise Foundation; Global Coalition for Africa; Henry L. Stimson Center; Honorary Presidential Advisory Council on Investment in Nigeria; Indira Gandhi Memorial Trust; InterAction Council; International Irrigation Management Institute; National Committee on United States-China Relations; Overseas Development Council; Rockefeller Foundation; Trilateral Commission; Urban Institute; World Bank; World Food Prize Foundation; World Resources Institute; Arms control; Cuban Missile Crisis, 1962.; Economic development -- Developing countries; Education; Geopolitics; Hunger -- Developing countries; International relations; Nuclear weapons; Onchocerciasis; Peace; Population